STRUKTUR FORMAL KAKAWIN KUMUDAWATĪ - I Putu Wiyasa (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2021)
Kakawin Kumudawati is kakawin taken from the story of Tantri. Kakawin Kumudawati is a telltale about the friendship of a pair of geese and a pair of turtles at Kumudawati Lake. This kakawin is classified into Minor kakawin because Kakawin Kumudawati is a new Kakawin; hence it is interesting to be studied in terms of the formal structure. Several formal structures of the kakawin are studied, namely, guru laghu, wreta, matra, gana, canda, carik, pada, pupuh, and alamkara.The structure analysis of the Kakawin Kumudawati is done for knowing the regularity of Kakawin Kumudawati in the guru – laghu, wretta – matra, pada and Gana principles. Guru and Laghu in the Kakawin Kumudawati are composed of three groups into one unit called Gana. Thus, Gana units are arranged into Mantra. The total of the words (Wreta) and Mantra form Canda. The compositions of Canda were written into the old Javanese language formed Kakawin Kumudawati. Kakawin Kumudawati uses five metrum, namely, Jagadhita, Basantatilaka, Kilayumenedeg, Rajani, and Indrawangsa metrum.